Aggregate supply and demand analysis/ by Paul Davidson and Eugene Smolensky - "Davidson, Paul" (New York, 1964)
The issues by no means resolved, but policy makers throughout the free world are acting on the conviction that the price level is related to the money wage rate. There is ample theoretical support for this belief. Keynes himself, the cambridge economists close to keynes, Hicks, and Weintaraub, have ereceted the appropriate theoretical framework albeit not in terms or places that make it readily comprehensible or available to the beginning student.
Keywords: Supply and demand